PERANCANGAN SOCIAL MEDIA MARKETING SEBAGAI MEDIA PROMOSI PADA BOMBO UAI MERCH - Deniar Reina Domassang; Syamsuddin Syamsuddin; Ahmadi Usman (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2022)
This research aimed to produced social media marketing as a promotional media at Bombo Uai Merch that is easy to use/applied as well as effective and efficient. The research method used is a design research method with the following stages or procedures: 1) Needs Analysis, 2) Data Collection, 3) Design, 4) Results, 5) Publication (posting), 6) Feedback. Furthermore, the data collection techniques used are: 1) Observation, 2) Interview, 3) Documentation. The data analysis technique used is descriptive qualitative data analysis. In this study, it was found that the results of the social media marketing design as a promotional media for Bombo Uai Merch included the use of 4 pillars (greeting, product info, promos, engagement), 21 Instagram feeds with captions and hashtags, 5 Instagram stories, 5 highlights, link tree beacons. ai, 7 Tiktok feeds with captions and hashtags, and 1 month SMC. The efficiency of social media marketing is seen from reaching a wider market share (audience) by saving time, energy and costs. Furthermore, the effectiveness of this social media marketing has had a good impact on sales with an increase of 80%. Context, communication, collaboration, and connection strategies were in accordance with the needs of followers.